2012
DOI: 10.1371/journal.pone.0033678
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginseng Polysaccharides on Influenza Viral Infection

Abstract: Ginseng polysaccharide has been known to have multiple immunomodulatory effects. In this study, we investigated whether Panax ginseng polysaccharide (GP) would have a preventive effect on influenza infection. Administration of mice with GP prior to infection was found to confer a survival benefit against infection with H1N1 (A/PR/8/34) and H3N2 (A/Philippines/82) influenza viruses. Mice infected with the 2009 H1N1 virus suspended in GP solution showed moderately enhanced survival rates and lower levels of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 36 publications
2
60
0
Order By: Relevance
“…This type of nonspecific interaction has been reported to be one of the anti-influenza mechanisms of epigallocatechin-gallate (32). Yoo et al (2012) also reported a comparable observation with ginseng polysaccharide treatment in mice, enhancing the survival rate with little impact on viral clearance (52). However, in prolonging survival, KV may have downplayed other contributory factors yielding to morbidity and mortality, such as the overzealous host's response dependent pulmonary immunopathology and loss of function as well as multiple organ failure (13,31).…”
Section: Discussionmentioning
confidence: 85%
“…This type of nonspecific interaction has been reported to be one of the anti-influenza mechanisms of epigallocatechin-gallate (32). Yoo et al (2012) also reported a comparable observation with ginseng polysaccharide treatment in mice, enhancing the survival rate with little impact on viral clearance (52). However, in prolonging survival, KV may have downplayed other contributory factors yielding to morbidity and mortality, such as the overzealous host's response dependent pulmonary immunopathology and loss of function as well as multiple organ failure (13,31).…”
Section: Discussionmentioning
confidence: 85%
“…3 The reports from early studies claimed that NGP was with many immune-enhancing properties, like activation of macrophage and NK cells, increasing secretion of cytokines such as IL-2, IL-12 and IL-6, production of antibody by B cell, regulating immune function, inflammatory or antiviral processes and response to stress and fatigue. [4][5][6][7] In…”
Section: Introductionmentioning
confidence: 99%
“…anti-inflammatory, anti-viral and anti-tumor activities have been reported [10,11,17,19,26,33,36,46]. Polysaccharides, incluing lentinan, a (1,3)-β-D-glucan, isolated and purified from Lentinus edodes has been licensed as an over-thecounter (OTC) dietary supplement and immunostimulatory drug in China [47].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous treatment of mice with GRPS was reported to exert a protective effect against Staphylococcus aureusinfected septic mice by suppressing early acute inflammation [34,35]. One recent study has also revealed that intranasal and intravenous administered GRPS showed a protective effect on influenza viral infection by lowering levels of inflammatory cytokine (IL-6) and lung viral titers [36]. The examination of GRPS immunopharmacological effect under LPS induced proinflammatory condition will shed light if GRPS can exhibit a beneficial prophylactic effect against LPS mediated immune and inflammatory disease conditions like endotoxemia.…”
Section: Introductionmentioning
confidence: 99%